2022
DOI: 10.1002/smtd.202200740
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Anomalous Local and Nanostructure Evolutions Induced by Lattice Oxygen Redox in Lithium‐Rich Cathodes

Abstract: Due to their accessible lattice oxygen redox (l‐OR) at high voltages, Li‐rich layered transition metal (TM) oxides have shown promising potential as candidate cathodes for high‐energy‐density Li‐ion batteries. However, this l‐OR process is also associated with unusual electrochemical issues such as voltage hysteresis and long‐term voltage decay. The structure response mechanism to the l‐OR behavior also remains unclear, hindering rational structure optimizations that would enable practical Li‐rich cathodes. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
4
5
0
Order By: Relevance
“…Nevertheless, the phase segregation in our Monte Carlo simulations reveals that Mn-deficient nanovoids are a signature of bulk O 2 formation. This structural description is consistent with observations of nanovoids in cycled cathodes from X-ray and neutron pair distribution function, small-angle X-ray and neutron scattering and electron microscopy experiments 14 17 , 48 . Some studies have attributed the formation of voids to the presence of oxygen vacancies, often in the context of oxygen loss 15 .…”
Section: Atomic To Nanoscale Mechanisms Of Oxygen Redoxsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, the phase segregation in our Monte Carlo simulations reveals that Mn-deficient nanovoids are a signature of bulk O 2 formation. This structural description is consistent with observations of nanovoids in cycled cathodes from X-ray and neutron pair distribution function, small-angle X-ray and neutron scattering and electron microscopy experiments 14 17 , 48 . Some studies have attributed the formation of voids to the presence of oxygen vacancies, often in the context of oxygen loss 15 .…”
Section: Atomic To Nanoscale Mechanisms Of Oxygen Redoxsupporting
confidence: 89%
“…Finally, to understand cathode behaviour over multiple cycles, it is necessary to consider thermodynamic factors. O-redox cathodes cycled towards a thermodynamic ground state increasingly exhibit both crystallographic site disorder 12 , 13 and nanoscale structural changes, such as the formation of nanovoids 14 17 . To model crystallographic disorder and nanoscale structural features, computational studies must search a vast configurational space to identify stable low-energy configurations while also using cell sizes large enough to capture relevant structural features.…”
Section: Mainmentioning
confidence: 99%
“…Nevertheless, the phase segregation in our Monte Carlo simulations reveals that Mn-deficient nanovoids are a signature of bulk O2 formation. This structural description 9 is consistent with observations of nanovoids in cycled cathodes from X-ray and neutron pair distribution function (PDF), small-angle X-ray and neutron scattering (SAXS, SANS), and electron microscopy experiments [16][17][18][19]52 . Some studies have attributed the formation of voids to the presence of oxygen vacancies, often in the context of oxygen loss 17 .…”
supporting
confidence: 83%
“…Finally, when modelling cathode behaviour after multiple cycles, thermodynamic considerations become more important. O-redox cathodes cycled towards a thermodynamic ground state exhibit crystallographic site disorder 14,15 and nanoscale structural changes, such as the formation of nanovoids [16][17][18][19] . To model disorder and nanoscale structural features, computational studies must search a vast configurational space to identify stable low-energy configurations and must use large enough cell sizes to capture the relevant structural features.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the Ru-LR-NMC sample shows charge capacity (372 mAh g –1 ) and discharge capacity (304 mAh g –1 ) (left panel), which are larger than that of 345 and 275 mAh g –1 observed in the LR-NMC sample. As reported in previous studies, the specific capacity can be ascribed to the charge compensation of cationic TM and anionic oxygen species. In addition, the ICE of the Ru-LR-NMC sample (81.4%) also exceeds that of the LR-NMC sample (79.5%) (right panel in Figure c). The higher capacity and coulombic efficiency of the Ru-LR-NMC sample is attributed to more reversible TM redox and oxygen-redox processes.…”
Section: Results and Discussionmentioning
confidence: 99%